2021
DOI: 10.3390/ma14175094
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Hydrothermal and Solvothermal Synthesis of Advanced Carbon Materials in Multidimensional Applications: A Review

Abstract: The adoption of green technology is very important to protect the environment and thus there is a need for improving the existing methods for the fabrication of carbon materials. As such, this work proposes to discuss, interrogate, and propose viable hydrothermal, solvothermal, and other advanced carbon materials synthesis methods. The synthesis approaches for advanced carbon materials to be interrogated will include the synthesis of carbon dots, carbon nanotubes, nitrogen/titania-doped carbons, graphene quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 111 publications
0
25
0
Order By: Relevance
“…Afterwards, the calcination process takes place on the precursor with a constant heating rate. TGA analysis has shown that the photocatalyst obtained by the solvothermal method has higher thermal stability than g-C3N4 and V 2 C. One of the advantages of the hydro/solvothermal method is the tunable morphology of the surfaces by controlling the reaction conditions [69][70][71][72]. In addition, by adjusting the pH during the solvent thermal technique, the generation of byproducts can be minimized or stopped [73].…”
Section: Hydro/solvothermal Methodsmentioning
confidence: 99%
“…Afterwards, the calcination process takes place on the precursor with a constant heating rate. TGA analysis has shown that the photocatalyst obtained by the solvothermal method has higher thermal stability than g-C3N4 and V 2 C. One of the advantages of the hydro/solvothermal method is the tunable morphology of the surfaces by controlling the reaction conditions [69][70][71][72]. In addition, by adjusting the pH during the solvent thermal technique, the generation of byproducts can be minimized or stopped [73].…”
Section: Hydro/solvothermal Methodsmentioning
confidence: 99%
“…Hydrothermal synthesis of functional materials can be conventionally performed in a wide temperature range, from room temperature to very high temperatures [77]. Since the first application of the hydrothermal process for nanomaterial synthesis in the 1990s, significant advances in understanding the physical-chemical features of this synthesis have been made [78]. As will be discussed in this section, the main parameters of the hydrothermal synthesis (i.e., initial pH of the precursor solution, duration, and temperature) define the process kinetics and the properties of the products, which are directly related with pressure in the system [79].…”
Section: Hydrothermal Synthesismentioning
confidence: 99%
“…For this reason, experimental investigation is privileged at the expense of computational models; researchers are rarely working to improve synthetic strategies, to achieve the design of protocols able to return monodispersed structures and more predictable properties. Besides this, optimization in terms of yields and the necessity to target low-cost and environmentally sustainable protocols are piloting laboratory activities as well [ 31 ].…”
Section: Graphene Quantum Dots Synthetic Strategiesmentioning
confidence: 99%